Cash Flow and Investment: Evidence from Internal Capital Markets - LAMONT, OWEN (Journal of Finance, 1997)
ABSTRACT Using data from the 1986 oil price decrease, I examine the capital expenditures of nonoil subsidiaries of oil companies. I test the joint hypothesis that 1) a decrease in cash/collateral decreases investment, holding fixed the profitability of investment, and 2) the finance costs of different parts of the same corporation are interdependent. The results support this joint hypothesis: oil companies significantly reduced their nonoil investment compared to the median industry investment. The 1986 decline in investment was concentrated in nonoil units that were subsidized by the rest of the company in 1985.